A dedicated pistonphone for absolute calibration of infrasound sensors at very low frequencies. (13th January 2016) - He, Wen; He, Longbiao; Zhang, Fan; Rong, Zuochao; Jia, Shushi
Abstract: Aimed at the absolute calibration of infrasound sensors at very low frequencies, an upgraded and improved infrasonic pistonphone has been developed. The pistonphone was designed such that a very narrow clearance between the piston and its guide was realized based on an automatically-centered clearance-sealing structure, and a large volume rigid-walled chamber was also adopted, which improved the leakage time-constant of the chamber. A composite feedback control system was applied to the electromagnetic vibrator to control the precise motion of the piston. Performance tests and uncertainty analysis show that the leakage time-constant is so large, and the distortion of the sound pressure is so small, that the pistonphone can be used as a standard infrasound source in the frequency range from 0.001 Hz to 20 Hz. The low frequency property of the pistonphone has been verified through calibrating low frequency microphones. Comparison tests with the reciprocity method have shown that the pressure sensitivities from the pistonphone are not only reliable at common frequencies but also have smaller uncertainties at low frequencies.